6t-15=-16+7t

Simple and best practice solution for 6t-15=-16+7t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6t-15=-16+7t equation:


Simplifying
6t + -15 = -16 + 7t

Reorder the terms:
-15 + 6t = -16 + 7t

Solving
-15 + 6t = -16 + 7t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-7t' to each side of the equation.
-15 + 6t + -7t = -16 + 7t + -7t

Combine like terms: 6t + -7t = -1t
-15 + -1t = -16 + 7t + -7t

Combine like terms: 7t + -7t = 0
-15 + -1t = -16 + 0
-15 + -1t = -16

Add '15' to each side of the equation.
-15 + 15 + -1t = -16 + 15

Combine like terms: -15 + 15 = 0
0 + -1t = -16 + 15
-1t = -16 + 15

Combine like terms: -16 + 15 = -1
-1t = -1

Divide each side by '-1'.
t = 1

Simplifying
t = 1

See similar equations:

| 3x+1*.5x+3=18 | | 0.3x-4=0.5+8 | | P^2+5x+6=0 | | 3x-(-x+2)=10-7x | | y^2-20y=-100 | | 11=3q+2 | | 5597+x=9000 | | -4*0+-4= | | 16y^2-56y=-49 | | -2*3=y-6 | | 3x+15=103 | | -2*0=y-6 | | 1.1y+0.3=1.3+0.3y | | 3n^2=12n | | -2*-3=y-6 | | -2*4=y-6 | | y-1.6667*-3=-2 | | y-1.6667*0=-2 | | y-1.6667*3=-2 | | 3a-(-1)=5 | | 2x^3-14x^2-60x=0 | | y-.66667*-3=-3 | | 2x-8y+6= | | y-.66667*3=-3 | | 6.2x-8=5.5 | | .66667*3= | | y-.66667*0=-3 | | x^2+3mk+9=0 | | 4(2x-1)+3(1-x)=4 | | .1x-2=-2.4 | | 9(7x+8)+3(x-10)= | | 2/3(x-2)=1 |

Equations solver categories